STUDY OF PREDISPOSING FACTORS OF RUPTURED UTERUS IN MARDAN MEDICAL COMPLEX (The Research of Medical Science Review, 2025)
Background: Uterine rupture is a critical obstetric complication that significantly contributes to maternal and fetal morbidity and mortality. Various factors, such as previous cesarean sections, preterm deliveries, and unbooked cases, are commonly associated with an increased risk of uterine rupture. Identifying these predisposing factors and understanding their impact can help in improving outcomes through early diagnosis and management, especially in resource-limited settings. Objective: To determine the predisposing factors associated with uterine rupture and evaluate their relationship with demographic characteristics. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from October 2024 to March 2025 at the Department of Obstetrics and Gynaecology, Mardan Medical Complex, Mardan. Methodology: A total of 214 women aged 18 to 40 years, with a singleton pregnancy and a gestational age of more than 30 weeks, were enrolled in the study. Data on demographic characteristics, predisposing factors (previous C-section, preterm delivery, and unbooked cases), and their association with age, gestational age, and parity were collected and analyzed. Results: The average age of participants was 30.23 ± 4.84 years, with an average gestational age of 37.67 ± 1.58 weeks and an average parity of 2.76 ± 1.47. Previous C-section was present in 42.5% of the cases, preterm delivery in 25.2%, and unbooked cases in 76.2%. A significant association was found between preterm delivery and gestational age (p < 0.001), with all preterm deliveries occurring in women with a gestational age of less than 37 weeks. Conclusion: This study concludes that previous C-section, preterm delivery, and unbooked cases are major predisposing factors for uterine rupture.